Irregular vascular pattern by contrast‐enhanced ultrasonography and high serum Lens culinaris agglutinin‐reactive fraction of alpha‐fetoprotein level predict poor outcome after successful radiofrequency ablation in patients with early‐stage hepatocellular carcinoma. (17th October 2016) - Takada, Hitomi; Tsuchiya, Kaoru; Yasui, Yutaka; Nakakuki, Natsuko; Tamaki, Nobuharu; Suzuki, Shoko; Nakanishi, Hiroyuki; Itakura, Jun; Takahashi, Yuka; Kurosaki, Masayuki; Asahina, Yasuhiro; Enomoto, Nobuyuki; et al.
Abstract: Radiofrequency ablation (RFA) is considered the most effective treatment for early‐stage hepatocellular carcinoma (HCC) patients unsuitable for resection. However, poor outcome after RFA has occasionally been reported worldwide. To predict such an outcome, we investigated imaging findings using contrast‐enhanced ultrasonography (CEUS) with Sonazoid and serum tumor markers before RFA. This study included 176 early‐stage HCC patients who had initially achieved successful RFA. Patients were examined using CEUS; their levels of alpha‐fetoprotein (AFP), Lens culinaris agglutinin‐reactive fraction of AFP (AFP‐L3), and des‐gamma‐carboxy prothrombin before RFA were measured. Sonazoid provided parenchyma‐specific contrast imaging and facilitated tumor vascular architecture imaging through maximum intensity projection (MIP). Kaplan–Meier analysis examined cumulative rates of local tumor progression, intrasubsegmental recurrence, and survival; factors associated with these were determined with Cox proportional hazards analysis. Local tumor progression ( n = 15), intrasubsegmental recurrence ( n = 46), and death ( n = 18) were observed. Irregular pattern in MIP classification and serum AFP‐L3 level (>10%) before RFA were identified as independent risk factors for local tumor progression and intrasubsegmental recurrence. These two factors were independently associated with poor survival after RFA (irregular pattern in MIP: hazard ratio, (HR) = 8.26; 95% confidence interval, (CI) = 2.24–30.3; P = 0.002 and AFP‐L3 > 10%: HR = 2.94; 95% CI = 1.09–7.94; P = 0.033). Irregular MIP pattern by CEUS and high level of serum AFP‐L3 were independent risk factors for poor outcome after successful RFA. The Patients with these findings should be considered as special high‐risk group in early‐stage HCC. Abstract : Vascular patterns of hepatocellular carcinoma (HCC) patients can be classified by contrast‐enhanced ultrasonography. Irregular patterns are associated with poor outcome after successful radiofrequency ablation in patients with early‐stage HCC.